Research Progress in Structure Evolution and Durability Modulation of Ir‐ and Ru‐Based OER Catalysts under Acidic Conditions - Zi, Yunhai; Zhang, Chengxu; Zhao, Jianqiang; Cheng, Ying; Yuan, Jianliang; Hu, Jue (Small (Weinheim an der Bergstrasse, Germany), 2024)
Green hydrogen energy, as one of the most promising energy carriers, plays a crucial role in addressing energy and environmental issues. Oxygen evolution reaction catalysts, as the key to water electrolysis hydrogen production technology, have been subject to durability constraints, preventing large‐scale commercial development. Under the high current density and harsh acid‐base electrolyte conditions of the water electrolysis reaction, the active metals in the catalysts are easily converted into high‐valent soluble species to dissolve, leading to poor structural durability of the catalysts. There is an urgent need to overcome the durability challenges under acidic conditions and develop electrocatalysts with both high catalytic activity and high durability. In this review, the latest research results are analyzed in depth from both thermodynamic and kinetic perspectives. First, a comprehensive summary of the structural deactivation state process of noble metal oxide catalysts is presented. Second, the evolution of the structure of catalysts possessing high durability is discussed. Finally, four new strategies for the preparation of stable catalysts, “electron buffer (ECB) strategy”, combination strength control, strain control, and surface coating, are summarized. The challenges and prospects are also elaborated for the future synthesis of more effective Ru/Ir‐based catalysts and boost their future application. This paper analyzes the catalyst dissolution process from both thermodynamic and kinetic perspectives. A comprehensive summary of the structural deactivation state process of noble metal oxide catalysts is presented. The catalyst structure evolution is made a summary and four strategies are proposed to improve its stability.